United Nations treaty bodies as a limited alternative for the protection of human rights in Spain - Martínez Pérez, Enrique J. (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The aim of this research is to analyze the legal status of pronouncements of expert bodies established under various human rights treaties at the universal level from an international and domestic standpoint, with particular emphasis on remedies and procedures to give legal effect to their decisions in Spain.